O saber linguístico em disciplinas do curso de pedagogia da Universidade Federal de Santa Maria (UFSM) - Dias, Adriele Delgado (2018)
The present study has the goal to analyze the meanings of the designations of disciplines which refer to linguistic knowing, of the Pedagogy Course at the Federal University of Santa Maria (UFSM), taking as a reference the theoretical assumptions of the Semântica do Acontecimento, of, Eduardo Guimarães, (2005). To contextualize our research, we present an panorama about the History of Linguistic Ideas (HIL) and on the History of Pedagogical Ideas in Brazil, with the purpose of situate the theoretical approach too, that dialogues with the studies of the HIL in Brazil, understanding how Linguistic becomes institutionalized and get disciplinary in the brazilian scenery. The goal of the research on this work is the set of disciplines related to the study of language that are part of the curriculum of UFSM's Pedagogy Course. On the analysis of selected disciplines as corpus of this research, we utilized the "Designation” as analytical category, highlighting the semantic function of the elements of articulation and specification inside each designation. We are interested in the designation as a mechanism for the attribution of sense, as well as your relationship with the text of each written registry of subjects. To this end, first, select six (6) subjects of the Course of Pedagogy of UFSM, cutting their designations and analyzing how they are structured and work semantically. Besides that, we have established a dialogue between the designations of disciplines with the proposed objectives, the programs and the bibliographies described, to understand how the set of such disciplines supports the pedagogical discourse of the Course and describes the area of linguistic studies in the formation of the future UFSM Pedagogue. The results show us that there is a worrying dispersion of linguist knowing over the Course of the Pedagogy of UFSM, in other words, the set of theories that supports the selected disciplines does not presents clarity the knowledge linguist that guides the formation of the Pedagogue.